Investigation and Analysis on Mental Health State of Breast Cancer Patients in China - Xiaoyan Liu; Wei Xu (International Journal of Psychotherapy Practice and Research, 2018)
Purpose: There are nearly 170,000 new cases of breast cancer in China every year, and this number is showing an increasing trend. Mental health plays an important role in promoting the physical rehabilitation of patients. Therefore, attention paid to their psychological problems needs to be reinforced. The current study aims to investigate the mental health states of the breast cancer patients and provides the references for their psychosomatic rehabilitation in the future work. Methods: A total of 643 breast cancer patients completed the whole study. A questionnaire survey on anxiety, depression, posttraumatic stress disorder (PTSD), and posttraumatic growth (PTG) was conducted in Jiangsu Women and Children Health Hospital. Results: 13.53% breast cancer patients had anxiety; 21.5% had depression; the prevalence of PTSD was 7.15%, while the prevalence of PTG was 26.12%; Anxiety levels in older patients were significantly lower than those in the other two groups; PTG levels in older patients were significantly lower than those in the other two groups. Conclusion: Breast cancer patients have certain emotional distress and stress symptoms, but they also experience psychologically positive changes. And age shows various differences on anxiety and PTG. Clinical medical personnel should pay attention to the patient's psychological rehabilitation when concerning about the physical rehabilitation of patients. Patients in different ages have different mental health problems, thus the medical staff shall provide differential nursing plans for them.
Keywords: breast cancer